Genome-Wide Identification and Expression Analysis of Calmodulin-Like Gene Family in Paspalums vaginatium Revealed Their Role in Response to Salt and Cold Stress - Meizhen Yang; Jingjin Chen; Tingting Liu; Leilei Xiang; Biao-Feng Zhou (Current Issues in Molecular Biology, 2023)
The calmodulin-like (CML) family is an important calcium (Ca2+) sensor in plants and plays a pivotal role in the response to abiotic and biotic stresses. As one of the most salt-tolerant grass species, Paspalums vaginatum is resistant to multiple abiotic stresses, such as salt, cold, and drought. However, investigations of PvCML proteins in P. vaginatum have been limited. Based on the recently published P. vaginatum genome, we identified forty-nine PvCMLs and performed a comprehensive bioinformatics analysis of PvCMLs. The main results showed that the PvCMLs were unevenly distributed on all chromosomes and that the expansion of PvCMLs was shaped by tandem and segmental duplications. In addition, cis-acting element analysis, expression profiles, and qRT–PCR analysis revealed that PvCMLs were involved in the response to salt and cold stress. Most interestingly, we found evidence of a tandem gene cluster that independently evolved in P. vaginatum and may participate in cold resistance. In summary, our work provides important insight into how grass species are resistant to abiotic stresses such as salt and cold and could be the basis of further gene function research on CMLs in P. vaginatum.